Rosa roxburghii tratt residue as an alternative feed for improving growth, blood metabolites, rumen fermentation, and slaughter performance in Hu sheep - Li, Huijie; Song, Xinyu; Wu, Wenxuan; Zhou, Chuanshe (Frontiers in Veterinary Science, 2024)
The utilization of agro-industrial by-products, such as fruit residues, presents a promising strategy for providing alternative feed to ruminants amidst rising prices and limited availability of traditional roughage. In this study, we investigated the effects of rosa roxburghii tratt residue, a local fruit residue in Guizhou province of China, on the growth, blood metabolites, rumen fermentation, and slaughter performance of Hu sheep. Ninety-six sheep were randomly divided into four groups, namely control, treatment 1, treatment 2, and treatment 3, and fed diets containing 0%, 10%, 20%, and 30% rosa roxburghii tratt residue, respectively. Feeding varying levels of rosa roxburghii tratt residue showed no significant differences in dry matter intake, average daily gain, or the ratio of dry matter intake to average daily gain. However, sheep in the group fed with 30% rosa roxburghii tratt residue showed the highest gross profit. Plasma albumin content was lower in groups fed with rosa roxburghii tratt residue-containing diets compared to the control group (p<0.05). Additionally, diet treatment 3 decreased plasma creatinine levels compared to control and treatment 1 (p<0.05).Sheep in treatment 2 and treatment 3 exhibited higher plasma high-density lipoprotein level than control and treatment 1 (p<0.05), as well as increased total cholesterol levels compared to control (p<0.05). There were no significant differences in other plasma metabolites. Rumen pH, N-NH3, volatile fatty acids, and methane levels did not differ significantly among the four groups. However, feeding diets treatment 2 and treatment 3 resulted in decreased water holding capacity and increased shear force compared to control and treatment 1 (p<0.05). Furthermore, pH, red chromaticity (a*), yellowness index (b*), and luminance (L*) were unaffected among the four groups of sheep.